2022
DOI: 10.3389/fnins.2022.878950
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Human-Specific Aspects of Neocortex Development?

Abstract: When considering what makes us human, the development of the neocortex, the seat of our higher cognitive abilities, is of central importance. Throughout this complex developmental process, neocortical stem and progenitor cells (NSPCs) exert a priming role in determining neocortical tissue fate, through a series of cellular and molecular events. In this Perspective article, we address five questions of relevance for potentially human-specific aspects of NSPCs, (i) Are there human-specific NSPC subtypes? (ii) Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
(88 reference statements)
1
8
0
Order By: Relevance
“…SVZ prominence is an additional excellent indicator of the mesocortical cingulate thickness, which diminishes towards the limbus, parallel with the CC development. Thus, our study further supports the general concept of the SVZ importance for primate cortex formation (Rakic and Nowakowski 1981 ; Haubensak et al 2004 ; Hevner 2007 ; Kelava et al 2012 ; Dehay et al 2015 ; Popovitchenko and Rasin 2017 ; Mora-Bermúdez and Huttner 2022 ). The fact that the primate characteristic SVZ is producing DPN—predominantly of pyramidal type, shows the tremendous importance of pyramidal neurons for the basic cortical architecture establishment in humans (Cajal 1911 ; Marin-Padilla 1983 ; Haydar et al 2000 ).…”
Section: Discussionsupporting
confidence: 88%
“…SVZ prominence is an additional excellent indicator of the mesocortical cingulate thickness, which diminishes towards the limbus, parallel with the CC development. Thus, our study further supports the general concept of the SVZ importance for primate cortex formation (Rakic and Nowakowski 1981 ; Haubensak et al 2004 ; Hevner 2007 ; Kelava et al 2012 ; Dehay et al 2015 ; Popovitchenko and Rasin 2017 ; Mora-Bermúdez and Huttner 2022 ). The fact that the primate characteristic SVZ is producing DPN—predominantly of pyramidal type, shows the tremendous importance of pyramidal neurons for the basic cortical architecture establishment in humans (Cajal 1911 ; Marin-Padilla 1983 ; Haydar et al 2000 ).…”
Section: Discussionsupporting
confidence: 88%
“…Such a process has been phrased as "a small step for the cell, a giant leap for mankind" [98]. A few case studies have shown consistent results, reporting that regulatory evolution contributed to a longer and faster proliferation phase of human NECs [100][101][102][103][104]. A modified version of the radial unit hypothesis emphasizes the increase in a derived stem cell population called outer or basal radial glial cells (oRGs or bRGs) in the fetal stage [105][106][107][108][109], when an excess of PSGs are expressed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of the six amino acid substitutions in these three proteins in modern humans appears to be unique. Therefore, this likely modern human‐specific set of six amino acids became a prime candidate to potentially explain the differences in AP metaphase duration and AP chromosome segregation fidelity observed between modern humans and chimpanzees, and potentially many other species, including Neanderthals (Mora‐Bermúdez & Huttner, 2022; Mora‐Bermúdez et al., 2016; Mora‐Bermúdez et al., 2022). Interestingly from an evolutionary point of view, and conveniently from an experimental point of view, all six ancestral amino acids are found not only in Neanderthals and Denisovans, but also in chimpanzees and other great apes, as well as many other species, including other primates, cetaceans, and, notably, rodents.…”
Section: Modern Human Versus Neanderthal Differences In Neocortical N...mentioning
confidence: 99%